Facile Synthesis of Copper Nanocubes in Aqueous Phase for Catalytic Esterification Using Green-Conditions - Al-Zubaidi, Hazim A; Al-Bassam, Ahmed Z. M.; Alabdullah, Sahar S. M. (Iraqi Journal of Science, 2024)
This work demonstrated a simple and environmentally friendly method for synthesizing silica-supported copper nanocubes (CuNCs/SiO2). The copper nanocubes, with a size of 15 ± 5 nm, were synthesized using green reagents and conditions. Ascorbic acid, water, and di-n-butyl sulfide were employed as reducing agent, solvent, and stabilizing ligand, respectively. The designed nanoscale catalyst was utilized for the esterification of acetic acid to methyl acetate at room temperature. The catalyst exhibited high efficiency, converting 80% of the reactant to the desired product (methyl acetate) after 24 hours of reaction at room temperature. The size and shape of copper nanocubes were characterized by transmission electron microscopy (TEM) and X-ray diffraction to characterize the formation of copper nanocubes, while the esterification product was characterized using gas chromatography-mass spectrometry.